1998
DOI: 10.1021/ja973159t
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Nuclear Magnetic Resonance Spectroscopic and Quantum Chemical Investigation of 13C and 17O Chemical Shift Tensors, 17O Nuclear Quadrupole Coupling Tensors, and Bonding in Transition-Metal Carbonyl Complexes and Clusters

Abstract: The carbon-13 and oxygen-17 nuclear magnetic resonance spectroscopic shielding behavior, as well as the oxygen-17 nuclear quadrupole coupling constants (NQCC), in the four metal−CO systems Fe(CO)5, Fe2(CO)9, Ni2(η5-C5H5)2(CO)2, and Rh6(CO)16 have been investigated both experimentally and by density functional calculations. Characteristics of the spectroscopic observables and bonding for the most common types of metal−carbonyl coordination, μ1-, μ2-, and μ3-CO, may thus be compared in detail. There is generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 54 publications
1
30
0
1
Order By: Relevance
“…This approach basically exploits the fact that the isotropic chemical shifts of the backbone carbonyl, alpha, and beta 13 C spins of each amino acid residue are to varying extents sensitive to the local secondary structure of the protein. Although recent work by Oldfield and coworkers has placed structural interpretation of isotropic 13 C chemical shifts of proteins on a quantitative basis [17][18][19], in the past, analyses of structures using chemical shift data have been done empirically by comparing experimentally observed 13 C chemical shifts for backbone 13 C spins to a large body of data, derived via 13 C Cross Polarization/Magic Angle Spinning (CPMAS) experiments from polypeptides of known secondary structure in the condensed state. An excellent example of this type of analysis is the seminal work by Fernandez et al [20] who studied the structures of polyglutamic acid and polylysine adsorbed to hydroxyapatite and silica using 13 C CPMAS.…”
Section: Nmr Methods For the Study Of Protein Structure At Biomateriamentioning
confidence: 99%
“…This approach basically exploits the fact that the isotropic chemical shifts of the backbone carbonyl, alpha, and beta 13 C spins of each amino acid residue are to varying extents sensitive to the local secondary structure of the protein. Although recent work by Oldfield and coworkers has placed structural interpretation of isotropic 13 C chemical shifts of proteins on a quantitative basis [17][18][19], in the past, analyses of structures using chemical shift data have been done empirically by comparing experimentally observed 13 C chemical shifts for backbone 13 C spins to a large body of data, derived via 13 C Cross Polarization/Magic Angle Spinning (CPMAS) experiments from polypeptides of known secondary structure in the condensed state. An excellent example of this type of analysis is the seminal work by Fernandez et al [20] who studied the structures of polyglutamic acid and polylysine adsorbed to hydroxyapatite and silica using 13 C CPMAS.…”
Section: Nmr Methods For the Study Of Protein Structure At Biomateriamentioning
confidence: 99%
“…Oldfield and collaborators [222] presented a detailed experimental NMR study in the solid state and quantum chemical investigation of both d( 13 C) and d( 17 O) and chemical shift tensor elements in a variety of metal carbonyls containing l 1 , -l 2 , and l 3 -CO ligands (Scheme 3). The SOS-DFPT approach in its local-density Loc1 approximation [223] with IGLO-II and IGLO-III bases was used.…”
Section: Perturbation Theory Including Electron Correlation Effectsmentioning
confidence: 99%
“…Accurate shielding polarizabilities can be calculated [227,232,236] by the use of the derivative Hartee-Fock (DHF) approach (Table 12) (Table 12) indicate large contributions from the perpendicular dipole shielding polarizabilities A yy,z with opposite signs for 13 C and 17 O. It was concluded [237] that perturbation of CO by electric fields within proteins is the principal cause for the linear correlation observed between m C@O and d( 13 C) and/or d( 17 O) in heme pro- Table 10 Comparison of experimental a and computed isotropic shifts, d iso , shift tensor elements, d xx , d yy , d zz , and shift anisotropies j d zz À d xx j and jd yy À d xx j [222].…”
Section: Inter-molecular Electric Field Effectsmentioning
confidence: 99%
“…It has been shown that density functional theory [3] (DFT) calculations are capable of predicting such HFC tensors for organic radicals [4][5][6][7], whereas the treatment of transition metal systems is also possible but in general much more difficult [7][8][9][10]. There are also systematic DFT studies of QC tensors for different nuclei and molecules that demonstrate the reliability of such theoretical predictions [11][12][13][14][15][16][17][18][19]. These results suggest that quantum chemical calculations based on the (unrestricted) Kohn-Sham formalism can be the missing link between magnetic resonance data and molecular structure.…”
Section: Lntroductionmentioning
confidence: 99%
“…60) were used. As in many other studies [11,12,19,27,28] the nuclear quadrupole moments were not calibrated for the applied theoretical methods. Using the above mentioned values for QN it was possible to calculate the QCCs directly from the V= eigenvalues of the EFGs obtained from the computations.…”
Section: Quadrupole Coupling Tensormentioning
confidence: 99%